Strategi Bertahan Hidup Pelaku Usaha Penggilingan Padi Di Desa Kopiwangker Kecamatan Langowan Barat - Temo, Efraim Jermia; Ngangi, Charles Reijaaldo; Talumingan, Celsius (AGRI-SOSIOEKONOMI, 2023)
This study aims to describe the survival strategies of rice mill business actors in Kopiwangker Village, Langowan Barat District. This research was conducted from December 2022 to May 2023. This study uses 2 types of data, namely primary and secondary data. Sampling uses a saturated sample method where all members of the population are used as samples. The data analysis method used in this study is a descriptive method through a qualitative approach. The results showed that the two rice mill business actors in Kopiwangker Village, West Langowan Subdistrict, implemented three strategies to be able to meet family needs and survive, namely: 1) The active strategy carried out by rice mill business actors was by doing side jobs and utilizing family work force to increase income. 2) The passive strategy carried out by rice mill business actors is to minimize expenses by eating with makeshift side dishes, storing weapons as food reserves, buying cheap clothes when needed and taking traditional medicine or drug stalls and seeking treatment at the puskesmas. 3) The network strategy applied by rice mill business actors is by establishing relationships with rice farmers so that grain remains available besides asking for help when in trouble from relatives, cooperatives and banks when they need money.